Instructional Design for Accelerated Macrocognitive Expertise in the Baseball Workplace - Fadde, Peter J. (Frontiers in Psychology, 2016)
The goal of accelerating expertise can leave researchers and trainers in human factors, naturalistic decision making, sport science, and expertise studies concerned about seemingly insufficient application of expert performance theories, findings and methods for training macrocognitive aspects of human performance. Video-occlusion methods perfected by sports expertise researchers have great instructional utility, in some cases offering an effective and inexpensive alternative to high-fidelity simulation. A key problem for instructional designers seems to be that expertise research done in laboratory and field settings doesn’t get adequately translated into workplace training. Therefore, this article presents a framework for better linkage of expertise research/training across laboratory, field, and workplace settings. It also uses a case study to trace the development and implementation of a macrocognitive training program in the very challenging workplace of the baseball batters’ box. This training, which was embedded for a full season in a college baseball team, targeted the perceptual-cognitive skill of pitch recognition that allows expert batters to circumvent limitations of human reaction time in order to hit a 90 mile-per-hour slider. While baseball batting has few analogous skills outside of sports, the instructional design principles of the training program developed to improve batting have wider applicability and implications. Its core operational principle, supported by information processing models but challenged by ecological models, decouples the perception-action link for targeted part-task training of the perception component, in much the same way that motor components routinely are isolated to leverage instructional efficiencies. After targeted perceptual training, perception and action were recoupled via transfer-appropriate tasks inspired by in situ research tasks. Using NCAA published statistics as performance measures, the cooperating team improved from middling performance to first in their conference in Runs Scored and team Batting Average. This case suggests that, beyond the usual considerations of effectiveness and efficiency, there are four challenges to embedded training in the workplace setting —namely: duration, curriculum, limited resources, and buy in. In the case reported here, and potentially in many domains beyond sports, part-task perceptual-cognitive training can improve targeted macrocognitive skills and thereby improve full-skill performance.